Mathematical modelling of solid waste management - Ibrahim∗, M.O.; Abdurrahman†, N.O. (International Journal of Mathematical Analysis and Modelling, 2023)
Solid waste is anything that comes from domestic, commercial, or industrial sources that is no longer needed. It is deposited as undesired. Waste disposal did not become an issue when there were few habitations and a lot of open space. Waste disposal becomes a real concern in towns and cities when more individuals move there in pursuit of employment [6,12]. Using a set of ordinary differential equations, a mathematical model for managing solid waste is put forth in this study. The solution’s existence and uniqueness are proven. In order to simulate the sensitive parameter for solid waste management, the next-generation matrix is used to identify the basic reproduction number R0. It has been found that when waste production increases, so does the rate at which energy is produced from waste.